Navigating AI Integration in Islamic Enterprises: A Qualitative SWOT Perspective - Mughoyaroh, Syaviratul; Rahmatika, Arivatu Ni’mati; Widyaningsih, Bekti (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2025)
This study explores the integration of Artificial Intelligence (AI) within Islamic strategic management frameworks using a qualitative SWOT analysis approach. The objective is to assess how AI can be ethically and effectively applied in Islamic enterprises, ensuring alignment with Shariah principles such as tawhid (the oneness of God), the balance between worldly and spiritual goals, and the pursuit of mardhatillah (divine pleasure). Using systematic literature review and SWOT framework, this research identifies internal strengths such as ethical leadership and community orientation and external opportunities such as the global halal market while addressing technological limitations and potential threats like ethical ambiguity and regulatory gaps. The findings highlight the importance of ethical leadership, community-based innovation, and strategic partnerships in navigating AI integration. This study contributes to the discourse on Shariah-compliant digital transformation and offers practical recommendations for AI governance rooted in Islamic values.